Perturbation of gene frequencies in a natural population of Drosophila melanogaster: evidence for selection at the Adh locus. - McKenzie, J.A.; McKechnie, S.W.; Batterham, P. (Genetica, 1994)
The cellular population of Drosophila melanogaster at the Chateau Tahbilk Winery (Victoria, Australia) was perturbed for alcohol dehydrogenase (Adh) gene frequencies. Phenol oxidase (Phox) frequencies were also perturbed and monitored as a control. Subsequent gene frequency changes, together with information on population structure, indicated that selection acted on the chromosome regions of both loci. Adh gene frequencies returned to preperturbation levels in a predictable manner. A model in which the relative fitness of Adh phenotypes was determined by temperature-dependent specific activities of enzymes of Adh genotypes adequately accounts for the rate of gene frequency change at this locus. Thus temperature behaves as a selective agent in modulating Adh gene frequencies in this cellar environment.